Bottom-simulating reflector dynamics at Arctic thermogenic gas provinces: An example from Vestnesa Ridge, offshore west Svalbard - Plaza-Faverola, Andreia; Vadakkepuliyambatta, Sunil; Hong, Wei-Li; Mienert, Jurgen; Bünz, Stefan; Chand, Shyam; Greinert, Jens (Journal of Geophysical Research: Solid Earth, 2017)
An edited version of this paper was published by AGU. Copyright 2017 American Geophysical Union. Plaza-Faverola, A., Vadakkepuliyambatta, S., Hong, W.-L., Mienert, J., Bünz, S., Chand, S. & Greinert, J. (2017). Bottom-simulating reflector dynamics at Arctic thermogenic gas provinces: An example from Vestnesa Ridge, offshore west Svalbard. Journal of Geophysical Research - Solid Earth, 122(6), 4089-4105. https://doi.org/10.1002/2016JB013761. To view the published open abstract, go to https://doi.org/10.1002/2016JB013761 .